Family Presence Restrictions and Telemedicine Use in Neonatal Intensive Care Units during the Coronavirus Disease Pandemic - Mio Ozawa; Haruyo Sakaki; Xianwei Meng (MDPI AG, 2021)
We aimed to describe parental presence policy and telemedicine use in Japanese neonatal intensive care units (NICUs) before and during the coronavirus disease (COVID-19) pandemic. This cross-sectional study was performed through an online survey in 110 level III units from 19 November 2020 to 18 December 2020. Nurses' evaluation of the current situation (during COVID-19) was compared with their retrospective pre-COVID-19 (December 2019) evaluation. Responses were received from 52 NICUs distributed across all regions in Japan. The median allowed parental presence time decreased from 12 h to 1 h, and 29 NICUs allowed entry of parents simultaneously during COVID-19. There was an increase in the number of units providing telemedicine through telephone and online visits during COVID-19 compared to that before COVID-19 (from 2% to 19%). The hybrid design NICUs, with 11-89% of beds in single-patient rooms, allowed a longer parental presence time in the NICUs than those with ≥90% of beds in multi-bed rooms. The number of units implementing kangaroo care decreased during COVID-19 compared to that before COVID-19. The need for telemedicine increased among Japanese NICUs to mitigate the adverse effect of parental restriction and limited physical contact due to the COVID-19 pandemic.